Highly porous and interconnected starch-based scaffolds: production, characterization and surface modification - Pashkuleva, I. (2010)
A convenient and straightforward process for preparation of highly porous and interconnected !ber mesh scaffolds with 50 wt.% content of starch is described. The proposed methodology avoids some of the previous encountered problems associated with the processing of starch-based materials such as thermal degradation, starch entrapment in the material bulk and inability to control/minimise the thickness of the !bers obtained by melt spinning, or low porosity and lack of interconnectivity for the scaffolds obtained by extrusion or injection moulding with blowing agent. Topographical characterisation of the obtained !bers revealed rough surface commonly related with increased cell attachment and growth. The in vitro tests with osteoblast cell line con!rmed this trend and we observed higher cell number with increasing of the culture time. These results were also associated with protein adsorption from a complex solution where predominant adsorption of vitronectin over !bronectin was detected. Finally, a model modi!cation by plasma was also carried out in order to con!rm the versatility of these scaffolds by the possibility to further upgrade them via surface functionalisation. The in vitro tests con!rmed that osteoblast-like cells proliferate faster on the modi!ed scaffolds, which allows shortening the time needed for culturing prior to implantation.